Business cycle convergence in EMU: A first look at the second moment - Jesús Crespo-Cuaresma; Octavio Fernández-Amador (FIW - Research Centre International Economics, 2010)
We propose the analysis of the dynamics of the standard deviation of business cycles across euro area countries in order to evaluate the patterns of cyclical convergence in the European Monetary Union for the period 1960-2008. We identify significant business cycle divergence taking place in the mid-eighties, followed by a persistent convergence period spanning most of the nineties. This convergent episode finishes roughly with the birth of the European Monetary Union. A hypothetical euro area including all the new members of the recent enlargements does not imply a sizeable decrease in the optimality of the currency union. Finally, the European synchronization differential with respect to other developed economies seems to have been diluted within a global cycle since 2004.
Keywords: E32; E63; F02; 330; Business cycles; business cycle convergence; European Monetary Union